2013
DOI: 10.1002/art.37913
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Susceptibility to Childhood‐Onset Rheumatoid Arthritis: Investigation of a Weighted Genetic Risk Score That Integrates Cumulative Effects of Variants at Five Genetic Loci

Abstract: Objectives Children with rheumatoid-factor or anti-citrullinated peptide antibody positive juvenile idiopathic arthritis represent the childhood onset of RA (CORA). To test the hypothesis that adult-onset RA-associated variants are also associated with CORA, we investigated RA-associated variants at five loci in our CORA cohort. We also assessed the cumulative association of these variants in the susceptibility to CORA using a weighted genetic risk score (wGRS). Methods 155 children with CORA and 684 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Polyarticular RF-positive JIA was associated with TNFAIP3 rs10499194 (OR: 0.60 (0.44–0.83)), PTPN22 rs 2476601 (1.61 (1.11–2.31)), and STAT4 rs7574865 (OR 1.41 (1.06–1.87)) variants. It was notable that the association between TNFAIP3 rs10499194 and polyarticular RF-positive JIA in this study [76] was more pronounced than with adult RA, as the confidence intervals of the odds ratios did not overlap with those of a meta-analysis of RA [77]. Using the largest cohort of patients with polyarticular RF-positive JIA, this study demonstrated that TNFAIP3, STAT4 and PTPN22 variants were associated with RF-positive JIA in a similar magnitude and direction as had been observed in adult RA.…”
Section: Genetics Of Polyarticular Rf-positive Jiamentioning
confidence: 94%
See 2 more Smart Citations
“…Polyarticular RF-positive JIA was associated with TNFAIP3 rs10499194 (OR: 0.60 (0.44–0.83)), PTPN22 rs 2476601 (1.61 (1.11–2.31)), and STAT4 rs7574865 (OR 1.41 (1.06–1.87)) variants. It was notable that the association between TNFAIP3 rs10499194 and polyarticular RF-positive JIA in this study [76] was more pronounced than with adult RA, as the confidence intervals of the odds ratios did not overlap with those of a meta-analysis of RA [77]. Using the largest cohort of patients with polyarticular RF-positive JIA, this study demonstrated that TNFAIP3, STAT4 and PTPN22 variants were associated with RF-positive JIA in a similar magnitude and direction as had been observed in adult RA.…”
Section: Genetics Of Polyarticular Rf-positive Jiamentioning
confidence: 94%
“…In a study of 155 children with polyarticular RF-positive JIA and 684 healthy autoimmunity free controls, subjects were genotyped for 5 variants in the PTPN22, TRAF1/C5, STAT4 and TNFAIP3 loci, all of which have been associated with RA [76]. Polyarticular RF-positive JIA was associated with TNFAIP3 rs10499194 (OR: 0.60 (0.44–0.83)), PTPN22 rs 2476601 (1.61 (1.11–2.31)), and STAT4 rs7574865 (OR 1.41 (1.06–1.87)) variants.…”
Section: Genetics Of Polyarticular Rf-positive Jiamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, based on data from GWASs, we constructed both weighted and unweighted genetic scores242526. We aimed to firstly construct models that were easy to interpret but were valid for risk prediction.…”
mentioning
confidence: 99%
“…Polymorphisms within HLA and many other genes were evaluated for RA risk susceptibility, but had not been investigated intensively in children. To provide evidence that RA risk alleles would also be connected to CORA, Prahalad et al [81] examined RA SNPs in large set of children with CORA. CORA was most frequent among children of 11 years, and 85% of studied cases were females.…”
Section: Ra Biomarkersmentioning
confidence: 99%